Mecanismos de consulta, participación y cooperación para una estrategia española de cambio climático - Yábar Sterling, Ana (M+A. Revista Electrónica de Medioambiente, 2006)
The article is dedicated to analyze the mechanisms, bodies and institutions created by the public administrations –mainly on the scope of the Spanish Ministry of Environment- to implement and develop appropriate social participation and cooperation processes to implement climate change policies and measures with the purpose of drawing conclusions on its ability to harness its effectiveness to reach mitigation and adaptation objectives and, also, to enhance the Spanish strategy of Climate Change. The conventional economic development paradigm and a dominant social demand for public climate change policies nowadays are identified as the two main driving forces for those processes. Also, the normative framework in the EU and Spain for environmental information public accessibility and the UNFCCC requirements - article 6- are mentioned to evaluate there implication in the outcomes. The concluding chapter emphasizes the need for a National education, training and public awareness Programme for climate change focussing the three public administrations level mitigation and adaptation policies in a cost-effective way.